Feeding Broilers with Reduced Dietary Crude Protein or Reduced Soybean Meal Diets Has No Negative Impact on the Performance and Carcass Traits While Reducing the Feed Global Warming Potential - Bart Matton; Adriaan Verhelle; Lise Vlerick; Katrijn Keirsschieter; Behnam Saremi (Animals, 2025)
One way to reduce the environmental impact of the European poultry industry is to feed birds with low crude protein (CP) or low soybean meal (SBM) diets, leading to less SBM import. In this paper, the objective was to examine if low CP and a feed limitation of SBM could be applied to reduce the global warming potential (GWP) of feed without a negative impact of the performance and slaughter parameters. Male Ross 308 birds (n = 1350) were divided between six treatments in a completely randomized design. In a three-phase feeding system, the dietary CP was reduced either only in the finisher phase (from 19% to 17% CP), in the grower phase (from 20% to 19% CP) and finisher phase, or in the starter (from 21% to 20% CP), grower, and finisher phases. In two additional groups, SBM inclusion in feed was reduced in each life phase either to a maximum of 15% SBM (low) or 0% SBM (zero) compared to a positive control (PC) group based on Aviagen 2019 recommendations, modified to 112% for standardized ileal digestibility (SID) arginine (Arg) to lysine (Lys) and 38% for SID histidine (His) to Lys. Data were analyzed with R (Version 4.2.0) using linear regression models. Opteinics™ (Chemovator, Mannheim, Germany) was used to calculate feed GWP. Means were compared with multiple comparisons corrected with Tukey’s test. Low CP diets had no negative effect on performance, carcass weight, and breast meat weight compared to the PC irrespective of the phase in which CP reduction was initiated. Both zero and low SBM groups had superior body weight (p < 0.05), weight gain (p < 0.05), and FCR (p < 0.05) compared to PC at d35. The low and zero SBM groups had higher carcass weight (p < 0.05) and breast meat weight (p < 0.05) compared to the PC. Both low CP and limiting SBM inclusion in feed positively improved the feed GWP compared to the PC. In conclusion, low CP diets can be applied in broilers during a 35 d growth period or specific phases thereof, with no negative impacts on performance parameters. Low and zero SBM-based diets showed superior performance and carcass weight in comparison to a conventional SBM-driven diet. Both strategies can be used to reduce the GWP of feed.